1991
DOI: 10.1002/tera.1420440105
|View full text |Cite
|
Sign up to set email alerts
|

Target tissue specificity of retinoic acid‐induced stress proteins and malformations in mice

Abstract: Retinoic acid (RA) is teratogenic in rodents and also induces the synthesis of stress proteins in fetal mouse limb buds. To determine if the RA induction of stress proteins is target tissue specific, pregnant CD-1 mice were gavaged with 100 mg/kg RA on day 11 of gestation, and nuclei isolated from tissues susceptible to RA-induced malformations (target tissues) as well as nuclei isolated from nontarget tissues were examined for stress protein synthesis and malformations. Forelimb and hindlimb (target tissues),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…20). Our results have, however, clearly shown that the administration of RA significantly influenced the growth of rat fetuses, supporting the view that its effect is more complex and the heart is not the only target tissue (21). Furthermore, Ruberte et al (22,23) and Dolle et al (24) have shown that cellular RA-binding protein adjacent mesenchyme, and neural crest cells.…”
Section: Discussionsupporting
confidence: 87%
“…20). Our results have, however, clearly shown that the administration of RA significantly influenced the growth of rat fetuses, supporting the view that its effect is more complex and the heart is not the only target tissue (21). Furthermore, Ruberte et al (22,23) and Dolle et al (24) have shown that cellular RA-binding protein adjacent mesenchyme, and neural crest cells.…”
Section: Discussionsupporting
confidence: 87%
“…In GD13 mice, maternal exposure to retinoic acid resulted in cleft palate and stress proteins of 34-, 84-, and 90-kD accumulated in craniofacial tissue. In GD11 mice, hindlimbs and forelimbs are the only tissues malformed by retinoic acid treatment, and accumulation of stress proteins of 25-, 84-, and 90-kD were specific to those tissues (Anson et al, 1991). The above studies suggest that stressors increase hsp synthesis in the affected tissues.…”
Section: Discussionmentioning
confidence: 88%
“…However, both proteins contain the so-called α-crystallin domain that is shared by all members of the sHSP family [10]and that presumably is responsible for the chaperone-like activity. sHSPs as well as αB-crystallin appeared to be involved in intracellular changes during disease progression [11, 12]. Besides, in disease progression, αB-crystallin is also involved in reactive processes of astrocytes and oligodendrocytes in the central nervous system [13], development of astrocytic tumors [14]and in the development of benign tumors associated with tuberous sclerosis.…”
Section: Introductionmentioning
confidence: 99%